Mortality reduction with use of oral beta-blockers in patients with acute coronary syndrome - de Matos Soeiro, Alexandre (2016)
OBJECTIVES: Recent studies have revealed a relationship between beta-blocker use and worse prognosis in acute coronary syndrome, mainly due to a higher incidence of cardiogenic shock. However, the relevance of this relationship in the reperfusion era is unknown. The aim of this study was to analyze the outcomes of patients with acute coronary syndrome that started oral beta-blockers within the first 24 hours of hospital admission (group I) compared to patients who did not use oral beta-blockers in this timeframe (group II). METHODS: This was an observational, retrospective and multicentric study with 2,553 patients (2,212 in group I and 341 in group II). Data regarding demographic characteristics, coronary treatment and medication use in the hospital were obtained. The primary endpoint was in-hospital all-cause mortality. The groups were compared by ANOVA and the chi-square test. Multivariate analysis was conducted by logistic regression and results were considered significant when p